The Urgency Of Developing New Strategies: Adressing The Challenges Of Regional Language Learning In The Era Of Globalization - Fatikha, Asma Lailatul (Instructional Development Journal, 2025)
This study seeks to find and implement fresh approaches that would help to solve local language learning issues in the age of globalization. The dominance of global languages like English and Arabic has the potential to influence the existence of local languages, hence creative ideas such the integration of digital technologies, project-based learning and multicultural methods are requiredThe study examines the impact of globalisation on young people's interest in local languages and the importance of an appropriate educational environment. The final plans aim to increase educational motivation, preserve cultural identity and ensure the viability of local languages in the context of globalisation. This study employs Miles and Huberman interactive model analysis using a descriptive qualitative methodology involving data reduction, data presentation and conclusion drawing/verification. Interviews, observations, documentary research, and subsequently data reduction helped to keep the analysis's focus via means of data. Due to variances in the linguistic systems between the santri's native tongue and Arabic, local language interference in Arabic language learning becomes a major obstacle, particularly in phonological and morphological elements. Strong techniques to overcome this include extensive phonetic practice, contextual morphological approaches and the incorporation of technology such learning software and interactive media (Mayer, Cognitive Theory of Multimedia Learning). By lowering language barriers and raising motivation, multicultural approaches help to establish an inclusive learning environment (Banks, Multicultural Education). Furthermore, the language immersion approach works well for raising Arabic language competency (Krashen, Second Language Acquisition; Vygotsky, Sociocultural Theory), hence the mix of these techniques is projected to maximise learning and greatly lower integration.